Cortical Iron Regulation and Inflammatory Response in Alzheimer’s Disease and APPSWE/PS1ΔE9 Mice: A Histological Perspective - Mark D Meadowcroft; Mark D Meadowcroft; James R Connor; Qing X Yang; Qing X Yang (Frontiers in Neuroscience, 2015)
Disruption of iron homeostasis and increased glial response are known to occur in brains afflicted by Alzheimer’s disease (AD). While the APP/PS1 transgenic mouse model recapitulates the hallmark amyloid-beta plaque pathology of AD, it does so in a different neuronal mileu than humans. Understanding the iron characteristics and glial response of the APP/PS1 model is important when testing new treatment procedures and translating these results. Brain tissue from AD patients, APP/PS1 mice, and controls were stained for iron, H- and L-ferritin, microglia, astrocytes, Aβ40/42, and degenerating neurons. The histological data demonstrate differences in ferritin, iron distribution, gliosis, and Aβ plaque composition between APP/PS1 and AD tissue. Specifically, an association between focal iron deposition and Aβ plaques is found ubiquitously throughout the AD tissue and is not observed in the APP/PS1 mouse model. Ferritin, microglia, and astrocyte staining show differential response patterns to amyloid plaques in AD and the APP/PS1 tissue. Aβ 40 and 42 antibody and thioflavin staining demonstrate morphological differences in plaque composition. The histological data support the hypothesis that iron distribution, iron management, and glial response histologically differ between the APP/PS1 and AD brain. Acknowledging the caveat that there are distinct plaque, iron, and glial contrasts between the AD brain and the APP/PS1 mouse is crucial when utilizing this model.